2019
DOI: 10.1021/acs.joc.9b00735
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Complexity as a Driver for Chemical Process Innovation in the Pharmaceutical Industry

Abstract: A Perspective of our work in the development of innovative synthetic methods within the discipline of Process Research and Development is presented. Through an overview of some of the programs that we have worked on during the past decade, we have selected cases studies to illustrate the challenges faced in development of robust chemical processes for molecules on a multi-kilogram scale. The examples have been selected to demonstrate the innovative chemistry being developed within our laboratories with a focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 114 publications
0
58
0
4
Order By: Relevance
“…Alcohol syn-(�)-5 was then subjected to concentration dependent testing by the NIH DTP (Table 2). 2 Alcohol syn-(�)-5 demonstrated micromolar activity towards the range of cell lines, and was most potent towards MOLT-4 with an LC 50 value of 6.1 μM. Additionally, its activity towards HL-60(TB) at 8.3 μM is intriguing.…”
Section: Results Of the Initial Evaluation Are Shown Inmentioning
confidence: 98%
See 2 more Smart Citations
“…Alcohol syn-(�)-5 was then subjected to concentration dependent testing by the NIH DTP (Table 2). 2 Alcohol syn-(�)-5 demonstrated micromolar activity towards the range of cell lines, and was most potent towards MOLT-4 with an LC 50 value of 6.1 μM. Additionally, its activity towards HL-60(TB) at 8.3 μM is intriguing.…”
Section: Results Of the Initial Evaluation Are Shown Inmentioning
confidence: 98%
“…Drug discovery efforts often show bias towards flat, achiral molecules, however candidates containing multiple sp 3 atoms and stereogenic centers have been associated with increased clinical success. [1,2] Biological targets are inherently threedimensional structures, therefore ligands that extend in all three dimensions may increase interactions to improve potency, while reducing off-target binding. [3] For example, an increase in dimensionality of the core skeleton can be important for assisting appendage π systems to more effectively interact with binding sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent examination of molecules in clinical development indicated that the average molecular complexity of synthetic drug candidates has been increasing over time and serves as an important driver for innovation in the pharmaceutical industry. [1] This complexity is being driven by efforts to improve the bioactivity of the molecules through structural changes designed to improve binding, selectivity, solubility and other key physicochemical properties. [2] The search for new drugs with better efficacy and safetyprofiles has led to the rise of small molecule -biologics pairings like antibody drug conjugates, [3] synthetic 'large molecules' such as siRNA [4] and the emergence of new modalities including proteolysis targeting chimeras (PRO-TACS) that induce protein degradation.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Among this backdrop of diverse and complex synthetic targets, there is intense pressure to shorten drug development timelines in order to better serve patients and compete successfully in a global marketplace. [1] Accordingly, in order to afford rapid access to sufficient quantities of complex pharmaceutical intermediates and products, new and robust synthetic methods are needed. To meet these needs, chemical development in the pharmaceutical industry relies heavily on metal-catalysed processes to increase selectivity and efficiency, enhance reactivity and reduce E-factor in moving chemistry from the laboratory to the plant.…”
Section: Introductionmentioning
confidence: 99%